Advancing Gender Inclusive Tourism Planning: Infrastructure Improvements, Safety Measures, and Sector-wide Advocacy - Nilanjana Dasgupta Sur; Devika AJ (Calibrating Urban Livability in the Global South, 2024)
Tourism is a cornerstone of many economies worldwide, contributing significantly to economic growth and cultural exchange. However, the tourism industry has not been equitable, often leaving gender-excluded and diverse individuals marginalized and vulnerable. The Travel and Tourism Development Index (TTDI) framework has 17 different parameters. The World Economic Forum has ranked countries based on TTDI and had India rank 54 out of 117 countries in 2021. Berkshire Hathaway Travel Protection has been assessing India’s safety status for four years through its rankings of the world’s safest countries. In 2022, India ranked 37th for safety among the 42 most popular countries for travellers. These figures underscore the need for gender-inclusive tourism planning, infrastructure improvements, and addressing safety concerns, to address the multifaceted challenges faced by women and gender-diverse individuals while fostering their meaningful participation in the tourism sector. Studies show women outlive men by an average of 5.2 years, and hence they comprise a greater share of older persons in the world’s population. In 2023, women accounted for 55.7 percent of individuals aged 65 and above. So, it is necessary to address gender-inclusive planning with a focus on all age groups. The 2018 impact report by the World Travel & Tourism Council (WTTC) highlights the potential to generate up to 10 million jobs within the tourism sector by 2028, forecasting a rise from 42.9 million in 2018 to 52.3 million by 2028. Considering this potential and the forthcoming opportunities for employment generation, the paper emphasizes the importance of integrating a gender perspective and gender mainstreaming in India’s tourism industry. This approach also aligns with the United Nations Sustainable Development Goals of Gender Equality (Goal 5) and Decent Work and Economic Growth (Goal 8). The major gaps identified in the tourism industry, such as the collection of gender-disaggregated data, lack of human resources, and inadequate gender-inclusive infrastructure, also needed to be addressed. Therefore, this paper aims to present the imperative of gender-inclusive tourism planning as a fundamental drive for sustainable and responsible tourism development in India. It also advocates for research in policy development and practical implementation of gender-inclusive tourism planning, emphasizing the need for collaboration between governments, the tourism industry, stakeholders, and local communities to create a tourism sector that is inclusive, equitable, and sustainable for all.